The Bell Curve: An Essay Review - Culbertson, John C. (Education Policy Analysis Archives, 1995)
Occasionally a book out of academia will break from scholarly circles and enter into the mainstream market. On even rarer occasions, it will gain considerable notoriety before its initial publication. Richard Herrnstein and Charles Murray's The Bell Curve: Intelligence and Class Structure in American Life is such a book. Currently, it has entered the New York Times best- sellers list and appeared in most academic and mainstream periodical book reviews. Direct publicity for the book has also been strong. Although Herrnstein died September 24 of the past year, Murray has appeared on many popular television and radio talk shows.